“Enantiomorphs and Kant's neglected alternative:an argument for the non-spatiality of things in themselves” - Petrik, J. (ҚазҰУ хабаршысы. Философия, саясаттану және Мәдениеттану, 2018)
The author is the author of the Kant philosophy (Neglected Alternative).